2015
DOI: 10.1103/physrevb.92.094203
|View full text |Cite
|
Sign up to set email alerts
|

Controlling transmission eigenchannels in random media by edge reflection

Abstract: Transmission eigenchannels and associated eigenvalues, that give a full account of wave propagation in random media, have recently emerged as a major theme in theoretical and applied optics. Here we demonstrate, both analytically and numerically, that in quasi one-dimensional (1D) diffusive samples, their behavior is governed mostly by the asymmetry in the reflections of the sample edges rather than by the absolute values of the reflection coefficients themselves. We show that there exists a threshold value of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…. Assuming a uniform distribution of x 0 between 0 and L leads to a bimodal distribution of C n [50]. The bimodal distribution of C n and hence T n is in agreement with the formula proposed for isolated peaks in the transmission spectrum of one-dimensional (1D) samples using a resonator model associated with effective cavities of length ξ [50,51].…”
Section: Distribution and Scaling Of Modal Strengths In Transmissupporting
confidence: 85%
“…. Assuming a uniform distribution of x 0 between 0 and L leads to a bimodal distribution of C n [50]. The bimodal distribution of C n and hence T n is in agreement with the formula proposed for isolated peaks in the transmission spectrum of one-dimensional (1D) samples using a resonator model associated with effective cavities of length ξ [50,51].…”
Section: Distribution and Scaling Of Modal Strengths In Transmissupporting
confidence: 85%
“…We investigate the effect of interface reflections at this surface on the statistics of the TM. In some earlier studies, numerical and analytical results have been obtained on the effect of boundary reflections on transmission matrices [30,39,40]. In these studies it was shown that the distribution of transmission eigenvalues of the fully controlled TM is not very sensitive to surface reflection for moderate surface reflectivity.…”
Section: Analysis and Numerical Simulation Of Interface Effects Omentioning
confidence: 99%
“…Spatial light modulator and related technologies have enabled manipulation of light propagation in scattering media via shaping the incident wave-front field to tailor it to the specific configuration of scatters in the sample [8,24,25]. This * yamilov@mst.edu brought renewed attention to the nonlocal correlations as they were found to be related to such transport parameters as focusing contrast inside the medium [26] and energy deposition [20,23,[27][28][29][30][31][32][33][34][35]. The long-range correlation also affects total transmission via an optimized wave front with a limited degree of input control [21]; it is also a key factor determining the broadband transmission achievable in wave-front shaping [36].…”
Section: Introductionmentioning
confidence: 99%